Horace's Epodes : contexts, intertexts, and reception - Bather, Philippa; Bather, Philippa; Stocks, Claire; Stocks, Claire (Oxford University Press, 2016)
Covering a range of topics including the iambic tradition and aspects of gender, this collection of essays on the Epodes overturns the work's ill-famed reputation and reasserts its place as a valued member of Horace's literary corpus